Intracerebral gene therapy of aromatic L-amino acid decarboxylase deficiency with eladocagene exuparvovec. Statement of the Society for Neuropediatrics (GNP), the Working Group on Pediatric Metabolic Disorders (APS), the German Society of Neurosurgery (DGNC) and the German Society of Pediatrics and Adolescent Medicine (DGKJ) - Opladen, Thomas; Brennenstuhl, Heiko; Kuseyri Huebschmann, Oya; Call, Debora; Green, Kim; Schara, Ulrike; Rascher, Wolfgang; Hoevel, Annegret; Assmann, Birgit; Koelker, Stefan; Westhoff, Jens H.; Walter, Magdalena; et al. (Monatsschrift Kinderheilkunde, 2021)
Background: The autosomal recessive defect of aromatic L-amino acid decarboxylase (AADC) causes a severe combined deficiency of dopamine, serotonin and catecholamines. The clinical picture is characterized by truncal hypotonia, delayed or absent achievement of motor milestones, and oculogyric crises from infancy onwards. The response to conventional drug treatment is very limited, especially in severe cases. The intracerebral application of eladocagene exuparvovec, an AAV2-based gene therapy, which is expected to be approved in mid-2021, is the first available causal therapeutic approach.
CRIS-Team WoS Importer:2021-07-16